2010
DOI: 10.1098/rsif.2010.0413
|View full text |Cite
|
Sign up to set email alerts
|

Nano-mechanical properties of individual mineralized collagen fibrils from bone tissue

Abstract: Mineralized collagen fibrils (MCFs) are distinct building blocks for bone material and perform an important mechanical function. A novel experimental technique using combined atomic force microscopy and scanning electron microscopy is used to manipulate and measure the mechanical properties of individual MCFs from antler, which is a representative bone tissue. The recorded stress -strain response of individual MCFs under tension shows an initial linear deformation region for all fibrils, followed by inhomogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
85
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(97 citation statements)
references
References 31 publications
9
85
1
2
Order By: Relevance
“…This failure mechanism appears to be a biological response to delocalize damage and maintain structural integrity during large deformation. Keeping the fibrillar organization could also favor pullout mechanisms, which represent yet another energy dissipation mechanism at the tissue scale, as observed in mineralized tendon49 or at bone fracture surfaces 14, 50, 51…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This failure mechanism appears to be a biological response to delocalize damage and maintain structural integrity during large deformation. Keeping the fibrillar organization could also favor pullout mechanisms, which represent yet another energy dissipation mechanism at the tissue scale, as observed in mineralized tendon49 or at bone fracture surfaces 14, 50, 51…”
Section: Resultsmentioning
confidence: 99%
“…Previous idealized models of nascent collagen fibrils have shown that mineral provides additional strength, stiffness, and ultimate strain to the fibrillar structure 31. However, these simplified two‐dimensional models ignore some geometric features of the fibril and do not completely capture the macroscopic deformation mechanisms as exposed in recent experimental work 14. Therefore, the mesoscale model of mineralized collagen fibril needs further improvements.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental validation of the mechanical properties of bone at the nanoscale is also very challenging. Relevant experimental studies include atomic force microscopy measurements combined with electron microscopy imaging (SEM and TEM) (e.g., [58][59][60]) and tests on micropillars of bone at a µm scale [61][62][63]. Theoretical models can give valuable insights on bone's response at the nanoscale and the structure-property relations of bone in general.…”
Section: Modeling Of Bone At Nanoscale Various Geometric Modelsmentioning
confidence: 99%
“…Por desgracia, el repertorio de pruebas mecánicas, disponibles para pequeños huesos de animales, es limitado debido a las limitaciones inherentes impuestas por el tamaño del hueso (Hang & Barber, 2011).…”
Section: Discussionunclassified